Synthesis of Some Hippuric Acid Substrate Linked Novel Pyrazoles as Antimicrobial Agents - Verma, Anil; Kumar, Vinod; Khare, Rajshree; Singh, Joginder (Asian Journal of Chemistry, 2019)
Escalating resistance of microorganisms to the currently accessible antimicrobial drugs has forced to synthesize some novel biologically active compounds as efficient alternates via economical substrates. Hence, hippuric acid was used as one of the starting materials to synthesize pyrazole derivatives. All the synthesized compounds were characterized by IR, NMR (1H & 13C) and mass spectral data. The antimicrobial potential of synthesized compounds has been explored against four bacterial and two fungal strains. Among the 12 compounds, 3 compounds 8j, 8k and 8l were found to exhibit prominent antimicrobial potential as compared with the standards ciprofloxacin and amphotericin-B.